Analyzing the teaching profile and competency-based training in online education: a case study of Ecuadorian professors - Castro Castillo, Graciela; Cárdenas-Cobo, Jesennia; Soldevilla, Marta Tenutto; Vidal-Silva, Cristian (Frontiers in Education, 2024)
In the global context of education, the online modality has become essential for expanding access to academic training. This study analyzes the teaching profile and competency-based training in online education among professors from Ecuador, a developing country in South America. An exhaustive documentary review and comparative analysis of the collected information were conducted using a qualitative and exploratory methodology. The documentary review involved a thorough search of academic documents, government policies, and study plans related to online education in Ecuador, with relevant and representative records selected. The comparative analysis enabled the identification of patterns, similarities, differences, and trends regarding the teaching profile and competency-based training in Ecuadorian online education. The results offer a 1 comprehensive view of how these dimensions have been addressed in Ecuador, serving as a reference for future research and contributing to developing and improving online academic programs in Ecuador and similar countries worldwide. Furthermore, they provide a valuable retrospective perspective on the evolution of online education in Ecuador, highlighting areas of strength and potential areas for improvement in this educational modality.